Kajian Sifat Kimia dan Uji Sensori Tepung Ubi Jalar Putih Hasil Pengeringan Cara Sangrai - Imam Santosa; Andinni Putri Winata; Endah Sulistiawati (CHEMICA: Jurnal Teknik Kimia, 2016)
Currently, the white-sweet potato (Ipomoea batatas L. Lam) has been developed as raw material of flour. The form of semi-finished sweet potato products is dry, durable, and has a long shelf life, such as dried cassava, fructose sugar, alcohol, various flour, starch. This form of semi-finished sweet potatoes can be developed into a variety of forms of processing that is done at the industrial level. The aims of this research were to determine the physical properties and examine the sensory test of sweet potato flour. The research was conducted by roasting at the temperature of 95-100 °C. The results showed that the flour had the water content of 7.63% and ash content of 1.998%. The sensory test performed in this study were color, odor, texture and shape of the white-sweet potato flour.